Intracranial atherosclerotic disease mechanistic subtypes drive hypoperfusion patterns. Issue 4 (30th April 2021) - Kim, Song J.; Morales, Jose M.; Yaghi, Shadi; Honda, Tristan; Scalzo, Fabien; Hinman, Jason D.; Raychev, Radoslav; Sharma, Latisha K.; Feldmann, Edward; Romano, Jose G.; Prabhakaran, Shyam; Liebeskind, David S.
Abstract: Background and Purpose: In symptomatic intracranial atherosclerotic stenosis (ICAS), borderzone infarct pattern and perfusion mismatch are associated with increased risk of recurrent strokes, which may reflect the shared underlying mechanism of hypoperfusion distal to the intracranial atherosclerosis. Accordingly, we hypothesized a correlation between hypoperfusion volumes and ICAS infarct patterns based on the respective underlying mechanistic subtypes. Methods: We conducted a retrospective analysis of consecutive symptomatic ICAS cases, acute strokes due to subocclusive (50%–99%) intracranial stenosis. The following mechanistic subtypes were assigned based on the infarct pattern on the diffusion‐weighted imaging: Branch occlusive disease (BOD), internal borderzone (IBZ), and thromboembolic (TE). Perfusion parameters, obtained concurrently with the MRI, were studied in each group. Results: A total of 42 patients (57% women, mean age 71 ± 13 years old) with symptomatic ICAS received MRI within 24 h of acute presentation. Fourteen IBZ, 11 BOD, and 17 TE patterns were identified. IBZ pattern yielded higher total T max > 4 s and T max > 6 s perfusion delay volumes, as well as corresponding T max > 4 s and T max > 6 s mismatch volume, compared to BOD. TE pattern exhibited greater median T max > 6 s hypoperfusion delay in volume compared to BOD. In IBZ versus TE, the volume difference between T max > 4 s and T max > 6 s (Δ T max > 4 s – T max > 6 s) was substantially greater. Conclusion: ICAS infarct patterns, in keeping with their respective underlying mechanisms, may correlate with distinct perfusion profiles.